Impact of hepatitis B and C virus infections on kidney transplantation: a single center experience - Santos, L (2009)
OBJECTIVE: The impacts of hepatitis C virus (HCV) and hepatitis B virus (HBV) infections on patient and renal graft survivals are controversial. This study sought to evaluate the effects of pretransplantation HCV and HBV infections on renal transplant patients and their grafts at our center. PATIENTS AND METHODS: We retrospectively examined 1224 renal transplantations performed between 1992 and 2006, including 28 HBsAg positive; 64, anti-HCV; 9, anti-HCV plus HBsAg positive; and 1123, negative for anti-HCV and HBsAg. The mean posttransplantation follow-up was 5.6 +/- 4.1 years. RESULTS: The prevalences of HBV infection were 6.2% in 1994 and 2.3% in 2006 and those of HCV infection were 6.8% in 1998 and 5.2% in 2006. The rejection rate was higher among HBV+ (46.4%) and HCV+ (40.6%) groups than the negative groups (31.5%), but it was not significant. There were no significant differences in patient and graft survivals among the groups. The major cause of patient death was liver failure among patients with concomitant HBV+ and HCV+ infections and cardiovascular disease among HCV+ and negative patients. CONCLUSIONS: There has been a decrease in the prevalence of recipients with hepatitis virus infections over the last 15 years. Patient and graft survivals were not affected by HCV or HBV infection.